Spiritual Education Mission in the Mufassirin Perspective - Syarif Syarif (Al-Albab, 2019)
Spiritual crisis is a factor leading to disorientation in today’s modern humans and the decline of morality of the nation. The low level of spirituality is caused by an educational approach that only focuses on the brain and ignores spiritual values. The Qur'an has actually affirmed the mission of spiritual education which should be used as a reference for the current education system. This article employs library research method through a comparison of the way the mufassirin interpret verses about the mission of spiritual education. The results show that the mission of spiritual education carried out by the Prophet Muhammad can be seen for example in Surat Al-Anbiya' verse 107, Surat Saba' verse 28 and Surat Al-Ahzab verse 21, namely rahmatan lil 'alamin (mercy to all creations). The prophet has brought evidence the truth to perfect the akhlậq, as well as to become the followers of uswah hasanah (perfect example) which must be imitated by all humans. Meanwhile, the stages of increasing spirituality in the Surat Luqman Verses 12-19, include: (1) instilling the tauhid values, (2) being filial to parents, (3) understanding the reciprocity of each deed, (4) command to worship, (5) introducing politeness in social life. Elements of spiritual education contained in Surat al-Muzzammil Verses 1-10 include qiyamul lail or night prayer, reciting the Qur’an in a tartil way, getting used to zikr, patience, jihad fi sabilillah or fighting on the path of Allah, and always praying and begging forgiveness from Allah.